2022
DOI: 10.1080/09503153.2022.2140132
|View full text |Cite
|
Sign up to set email alerts
|

Bruises in Premobile Infants: A Contested Area of Research, Policy and Practice

Abstract: This paper provides an analysis of the procedures adopted by statutory safeguarding partners throughout England in response to finding bruising in premobile infants. Against the backdrop of empirical research, we begin by challenging the view that bruising in premobile infants can be considered rare and thus suggestive of physical abuse. Then, within the procedure themselves, we point to differences in the definitions of what constitutes a premobile child, differences in the interpretation of research into bru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The fact that the pre-mobile infant had bruises made this pediatrician suspect a case of child abuse beforehand. However, Bilson described the following reasons for accidental bruises in children who were not yet able to roll over: bumping into the mother’s tooth, falling asleep on a dummy, banging themselves with a fist or rattle, or a toy that was dropped on the baby [ 42 , 43 ]. In this case, the pediatrician ignored a range of similar explanations offered by the parents and grandparents of the child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the pre-mobile infant had bruises made this pediatrician suspect a case of child abuse beforehand. However, Bilson described the following reasons for accidental bruises in children who were not yet able to roll over: bumping into the mother’s tooth, falling asleep on a dummy, banging themselves with a fist or rattle, or a toy that was dropped on the baby [ 42 , 43 ]. In this case, the pediatrician ignored a range of similar explanations offered by the parents and grandparents of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the work by Bilson [ 42 , 43 ], other studies have shown that it can be difficult to find a medical cause for bruising in very young infants, e.g., [ 44 , 45 , 46 , 47 ]. This, however, should not result in a wrong diagnosis of child abuse.…”
Section: Discussionmentioning
confidence: 99%